Trends of Expanded Clay Production and Use of Expanded-clay Concrete in Modern Construction - Serdiuk, V. R. (Visnyk of Vinnytsia Politechnical Institute, 2018)
In this article “Trends of expanded clay production and use of expanded-clay concrete in modern construction” the state of expanded clay and expanded-clay concrete production as a modern wall constructional-thermal insulating material in Ukraine and some other countries is discussed. Firstly, the general characteristic of technologically complex product of expanded clay, which requires the using of high-temperature production processes, is presented. Also, statistical information on volumes of expanded clay and expanded-clay concrete production in some countries of the world and historical information on its occurrence as a building material are analyzed. It was shown that the peak of expanded clay production dates backed to the 80s of the last century. The main directions of improvement legislative and regulatory framework of expanded clay and expanded-clay concrete production are described. Also, the author discloses the general reasons of reducing production of expanded clay and expanded-clay concrete. This paper is focused on calculations results of the thickness wall construction and comparative analysis of the main wall materials for compliance with the normative requirements of thermal resistance. Furthermore, the modern approaches forecasting of expanded-clay concrete strength have been analyzed. The indicator of constructive quality of expanded-clay concrete has been calculated. Likewise, the basic approaches to processing of building waste and main directions the recycling wastes of building production, in particular ceramic products are determined. This work has been done to evaluate certain technological possibilities for the processing of construction waste and its use in the production of building materials.